Penggunaan Akun Instagram @Tfpkopiwarun Sebagai Media Informasi Komunikasi Pemasaran TFP Kopi Warung Pasar Gede Solo - Utami, Alviana Cahyaning; Hindra Hastuti, Nurnawati; Mahar Rizqi, Fikriana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
ABSTRACTThis study aims to analyze the use of the Instagram account @tfpkopiwarun as a medium for marketing communication information for TFP Kopi Warung Pasar Gede Solo. This research is a qualitative descriptive study, with the subject being the Instagram account @tfpkopiwarun. Informants for this study were selected using purposive sampling techniques, resulting in five informants, the account manager of @tfpkopiwarun, Meynar Intan. Three followers of @tfpkopiwarun, and one visitor to TFP Kopi Warung Pasar Gede Solo who is not a follower of @tfpkopiwarun. Data collection methods used include observation, interviews, and documentation. Data analysis was carried out descriptively interactively through data collection, data condensation, data presentation, and conclusion drawing. Data validity was ensured through triangulation techniques. The results indicate that the Instagram account @tfpkopiwarun is effective in disseminating information that is both understandable and visually appealing. Posts made by the account are well received by followers, as evidenced by interactions such as likes, comments, and information sharing. The account manager consistently provides accurate and reliable information and posts with regular frequency. The attractiveness of the messages is enhanced through content selection, photography and editing, and informative caption writing.Keywords : Instagram, information media, marketing communication.